PENGARUH GAYA KEPEMIMPINAN DAN BUDAYA ORGANISASI TERHADAP KINERJA KARYAWAN MELALUI KEPUASAN KERJA KARYAWAN SEBAGAI VARIABEL INTERVENING - jurnalpps pps; Silahul Mukmin; Indra Prasetyo (Jurnal Manajerial Bisnis, 2021)
The aimed of this study was to determine the effect of leadership style and organizational culture on employee performance through job satisfaction as an intervening variable. This type of research used quantitative research. Data collected used questionnaires and documentation with a total sample of 50 people.. Data analysis techniques used are descriptive analysis and path analysis. The results showed that 1) Significant influential leadership style on job satisfaction. 2) Organizational culture has a significant effect on job satisfaction. 3) Leadership style has a significant effect on employee performance. 4) Organizational Culture signifies significant effect on employee performance. 5) Job satisfaction has a significant effect on employee performance. 6) Job satisfaction is an intervening variable between leadership style and employee performance because the value of indirect influence is greater than direct influence. 7) Job satisfaction is an intervening variable between organizational culture on employee performance because the value of indirect influence is greater than direct influence. Keywords: leadership style, organizational culture, employee performance, employee satisfaction